LITERASI BIMBINGAN DAN KONSELING UNTUK PENINGKATAN MINAT BACA SISWA DI SDI WAEWARU - Maria Tevian Wonga; Marsianus Meka; Konstantinus Dua Dhiu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The purpose of this study was to determine the literacy movement through guidance and counselling towards increasing students' interest in reading at SDI Waewaru. The type of research conducted is descriptive qualitative research where the data used is through the method of direct interviews with students and teachers in the school environment and making observations and observing phenomena that occur in real life in the school environment. This research was conducted at SDI Waewaru, Aimere sub-district, Ngada Regency. This activity was carried out to all students at SDI Waewaru, with a total of 103 students. The results of the research conducted at SDI Waewaru show that guidance and counselling is very influential for students' literacy skills and interest in reading.